PERAN PEMERINTAH INDONESIA DALAM MENGATASI PERILAKU LESBIAN TENAGA KERJA WANITA DI HONGKONG (2007-2009) - Nadiya Afifah; Pakpahan Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study examines the role of the indonesian government in dealing with thephenomenon of lesbian women in Hongkong workforce (2007-2009). This research is a greatstudy in International Relations which seeks to look at the role of government and the relationto the dynamics of migrant workers (TKI), particularly the behavior of TKW in Hongkong.Hongkong is a country that receives a lot of opportunities maids from Indonesia. With themultitude of TKW in Hongkong appear various problems either violence or harassment.There is one problem that arises within the maids in Hongkong which is a new phenomenonthat emerged quickly jumped in number from year to year which TKW relationship withfellow maids called "Lesbian".This phenomenon is motivated by the problems previously experienced in the past in,environmental and cultural factors as well as social interaction is done in Hongkong. Toreview these cases, the researcher uses role theory to support this research. In the theory ofroles according to John Wahlke there are two skills that are useful to the political analysis ofpolitical actors, namely political actors and government TKW.This study was ended on the role of government is to build an organization of Indonesianmigrant workers to be used as a grievance and problems faced by migrant workers inHongkong. Some of the Organization are: the Indonesian Migrant Workers Union (IMWU),Hongkong Indonesia Labor Coalition (KOTKIHO). Unity Da'wah Victoria (PDV) andCombined Muslim Indonesia migrant workers (GABMMI).Keywords: Lesbian, role of Government, TKW